Макарычев алгебра 7 класс решебник гдз

Номер 1079

Условие:

Упростите выражение:
а) (2x - 3у)2 + (2x + 3у)2;    б) (2х + 3у)2 - (2х - 3у)2;
в) 2(x/2 + y/4)2 + (2x - y)2; г) 3(x/3 + y/9)2 - (3x - y)2.

 

Ответ:

а) (2x - 3у)2 + (2x + 3у)2 = 4x2 - 12xy + 9y2 + 4x2 + 12xy + 9y2 = 8x2 + 18y2;
б) (2х + 3у)2 - (2х - 3у)2 = 4x2 + 12xy + 9y2 - 4x2 + 12xy - 9y2 = 24xy;
в) 2(x/2 + y/4)2 + (2x - y)2 = x2/2 + xy/2 + y2/8 + 4x2 - 4x2 - 4xy + y2 = 4 1/2x2 - 3 1/2xy + 1 1/8y2;
г) 3(x/3 + y/9)2 - (3x - y)2 = x2/3 + 2/9xy + y2/27 - 9x2 + 6ху - у2 = -8 2/3x2 + 6 2/9xy - 26/27y2.